Computational fluid dynamics (CFD) mesh independency technique for a propeller characteristics in open water condition - Nakisa, M. (2015)
This paper numerically investigated mesh refinement method in order to obtain a mesh independent solution for a marine propeller working in open water condition.Marine propeller blade geometries, especially of LNG carriers, are very complicated and determining the hydrodynamic performance of these propellers using experimental work is very expensive, time consuming and has many difficulties in calibration of marine laboratory facilities. The present research workhas focused on the hydrodynamic propeller coefficients of a LNG carrier Tanaga class such as Kt, Kq and η, with respect to the different advance coefficient (j). Finally, the results of numerical simulation in different mesh density that have been calculated based on RANS (Reynolds Averaged Navier Stocks) equations, were compared with existing experimental results, followed by analysis and discussion sections. As a result the maximum hydrodynamic propeller efficiency occurred when j=0.84.